PENGARUH EKSTRAK BUNGA EKOR KUCING (Acalypha hispida Burm. F) TERHADAP PERTUMBUHAN Candida albicans (Y116) - Hildayati, Umi; Wardoyo, Elvi Rusmiyanto Pancaning; Rahmawati, Rahmawati (Universitas Tanjungpura, 2020)
Candida albicans is an opportunistic pathogenic yeast that causes the infection candidiasis. Ekor kucing flower (Acalypha hispida) is one of the plants that has a potential for antifungal activity. This research aims to determine the power of methanol extract of ekor kucing flower against the growth of C. albicans (Y116) and to discover the perfect concentration of methanol extract of ekor kucing flower to inhibit the growth of C. albicans. This study used the disk-diffusion agar method by utilizing the paper disc. This research is made up of 3 treatmentsÂ of methanol extract concentration of ekor kucing flower by 0 (DMSO 10%); 0.3; and 0.5 g/ml. The results of the study show that the concentration of methanol extract of ekor kucing flower offers an antifungal activity against the growth of C. albicans. Antifungal activity is represented with the result of a zone of inhibition. The ideal concentration inhibit the growth of C. albicans is 0.3 g/mL with inhibitory zone diameter 10.18 mm.